PEMAHAMAN TRINITAS DALAM TEOLOGI DAN IMPLIKASINYA BAGI IMAN KRISTEN - Rima Pagiling; Wista Pasambo, Wisti Pasambo, Novita Pasoloran, Yosfina Tandi Belo (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2026)
This study discusses the understanding of the doctrine of the Trinity in Christian theology and its implications for the faith life of believers. The doctrine of the Trinity, which states that God is one essence in three persons, namely the Father, the Son, and the Holy Spirit, serves as a fundamental foundation that not only explains the nature of God but also forms the basis of relationship and love in the life of faith. Through a qualitative theological approach and literature analysis, this study explores and analyzes how the understanding of the Trinity influences the practices of prayer, worship, and the daily lives of Christians. The results show that the doctrine of the Trinity is not only an important theological aspect but also a practical source of inspiration that strengthens the relationship between humans, God, and others in a life full of meaning and love.